(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Guna (attribute) is one of the causes for the efficacy of any substance and is inseparable concomitance with substance. Ruksha guna is one of the Vata gunas perform the action of Dosha soshana karma (absorption). In broad perspective Soshana karma may be taken as the exchange of various materials in between the cell and respective environment. No study in context to the assessment of Ruksha guna has yet been carried out in modern perspective in the field of Ayurveda. The present study, was planned to evaluate the etymological and syntactical derivation of the Guna of Vata dosha, the biophysical and molecular basis of the Ruksha guna. and to validate the assessment criteria of Ruksha guna. For the assessment of Ruksha guna, observed the relative changes in the skin pH and skin moister with the level of vascular osmolality. These parameters are indicators of skin hydration in both healthy (with Dhatu samya lakshana) and Twaka rukahata condition (as patient with Rakta kshaya lakahana). Comparing the relation of skin pH and skin hydration along with vascular osmolality in both group to reveal the relation between osmolality and Rukstwa (roughness) the study was conducted. The study concluded that Ruksha guna of Vata dosha is critical requirement to make cell alive or to sustain the cellular homeostasis by its absorption and transport mechanism. Rakta kshaya may be correlated with decrease in the amount of circulatory hemoglobin in plasma. Rukshatwa therefore correlate with plasma osmolality and assessed by skin pH and hydration.